Observing the SO2 and Sulfate Aerosol Plumes From the 2022 Hunga Eruption With the Infrared Atmospheric Sounding Interferometer (IASI) - Pasquale Sellitto; Richard Siddans; Redha Belhadji; Elisa Carboni; Bernard Legras; Aurélien Podglajen; Clair Duchamp; Brian Kerridge (Geophysical Research Letters)
Abstract The Hunga volcano violently erupted on 15 January 2022, producing the largest perturbation of the stratospheric aerosol layer since Pinatubo 1991, despite the initially estimated modest injection of SO2. This study presents novel SO2 and sulfate aerosol (SA) co‐retrievals from the Infrared Atmospheric Sounding Interferometer, and uses them to quantify the initial progression of the Hunga plume. These observations are consistent with rapid conversion of SO2 (e‐folding time: 17.1 ± 4.3 days) to SA, with an injected burden of >1.0 Tg SO2. This points at larger SO2 injections than previously thought. A long‐lasting SA plume was observed, with two separate build‐up phases, and with a meridional dispersion of marked anomalies from the tropics to the higher southern hemispheric latitudes. A limited (∼20%) SA removal was observed after 1‐year dispersion. The total injected SA mass burden was estimated at 1.6 ± 0.5 Tg in the total atmospheric column, with a build‐up e‐folding time of about 2 months.